Sediment echosounder raw data (Atlas Parasound P70 echosounder entire dataset) of RV POLARSTERN during cruise PS127 - Weigelt, Estella; Esper, Oliver; Gebhardt, Andrea Catalina (PANGAEA, 2025)
Sediment echosounder (Teledyne Parasound P70 echosounder) data are generally retrieved to get information on the characteristics of the upper tens of meters of the sub-seafloor. Raw primary high frequency (PHF) and secondary low frequency (SLF) echo sounding data were retrieved during POLARSTERN cruise PS127 and are archived here in ASD and PS3 format. Data were collected as part of a training program. The entire dataset of cruise PS127 is archived here, with data collected between Bremerhaven and Las Palmas.
Keywords: PARASOUND; sediment echosounder